2020
DOI: 10.1038/s41598-020-69738-w
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic effects of antihyperglycemic agents and mortality: meta-analysis of randomized controlled trials

Abstract: The effects of antihyperglycemic medications on cardiovascular events and mortality are heterogeneous and their effects on intermediate factors might explain these differences. This systematic review explores the relationship between metabolic factors, mechanism of action, and mortality effects of antihyperglycemic medications in type 2 diabetes. Randomized trials assessing the effects of antihyperglycemic medications on all-cause or cardiovascular mortality in type 2 diabetes were included. Myocardial infarct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 73 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…SGLT2i also may exert anti-inflammatory effects via increased fat utilization, shifts in energy metabolism, increases in hematocrit, selective reduction of interstitial volume with minimal changes in blood volume, and maintenance of cytosolic pH ( 16 , 35 ). In addition, both SGLT2i and GLP1-RA are associated with reduced risk of cardiovascular events and chronic kidney disease progression in patients at high risk ( 14 ), a population associated with higher mortality in individuals with COVID-19 ( 2 ). A recent population-based cohort study in Denmark compared the association of GLP1-RA and DPP4-i use and COVID-19 outcomes with that of SGLT2i use and COVID-19 outcomes and found that the use of incretin-based therapies was not associated with improved clinical outcomes ( 36 ), although statistical power was limited by a small sample size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SGLT2i also may exert anti-inflammatory effects via increased fat utilization, shifts in energy metabolism, increases in hematocrit, selective reduction of interstitial volume with minimal changes in blood volume, and maintenance of cytosolic pH ( 16 , 35 ). In addition, both SGLT2i and GLP1-RA are associated with reduced risk of cardiovascular events and chronic kidney disease progression in patients at high risk ( 14 ), a population associated with higher mortality in individuals with COVID-19 ( 2 ). A recent population-based cohort study in Denmark compared the association of GLP1-RA and DPP4-i use and COVID-19 outcomes with that of SGLT2i use and COVID-19 outcomes and found that the use of incretin-based therapies was not associated with improved clinical outcomes ( 36 ), although statistical power was limited by a small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Two classes of antihyperglycemic medications, glucagon-like peptide 1 receptor agonists (GLP1-RA) and sodium–glucose cotransporter 2 inhibitors (SGLT2i), have been associated with a reduction of cardiorenal events and mortality in large trials of cardiovascular outcomes ( 5 8 ), heart failure ( 9 , 10 ), and renal outcomes ( 11 , 12 ) in populations at high risk of cardiorenal events. Benefits associated with these medications appear most pronounced among individuals with type 2 diabetes and comorbid cardiovascular disease, heart failure, chronic kidney disease, and obesity ( 1 , 2 , 4 , 13 , 14 ), conditions that also incur the highest risk for severe COVID-19. Additionally, plausible mechanisms for the protective effects of GLP1-RA and SGLT2i in COVID-19, independent of their glycemic effects, have been speculated ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is possible that these beneficial effects are not due to glucose lowering but rather to other concomitant treatments, such as antihypertensive agents [ 11 , 25 ]. Second, as known from the ACCORD and ADVANCE trials, achieving good blood glucose control could be at the cost of the number of hypoglycemic events and weight gain and thus not result in reduced mortality [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, two meta-analyses reported that SGLT-2i was associated with reduced risk of cardiovascular events and chronic kidney disease progression in diabetic patients. 57,58 SGLT-2i was mainly adopted in nonsevere patients with COVID-19. 59 This study has several limitations.…”
Section: Discussionmentioning
confidence: 99%